Keeping and breeding of andean milksnake (Lampropeltis triangulum andesiana) - Gál, János; Pak, Veronika; Marosán, Miklós (Animal welfare, Ethology and Housing Systems (AWETH), 2010)
The popularity of Andean milk snakes among reptile enthusiasts has grown a great deal in recent times. Presently, there is a huge array of subspecies of the Lampropeltis triangulum species which are bred and kept in captivity. The most common subspecies include L. t. sinaolae, L. t. campbelli and a representative of the giant subspecies, the Honduran milksnake (L. t. hondurensis) (Mara, 1994; Gál, 2002). The Andean milksnake (L. t. andesiana) is another significant representative of the giant subspecies of milksnakes next to L. t. hondurensis, L. t. gaigae, L. t. abnorma and L. t. micropholis (Thissen & Hansen, 1996).